Computerized Senior Citizen Health Monitoring using Mobile Application - Ahmad Yani, Nursyafiqah Aisyah; Zolkipli, Mohamad Fadli (SOTVI, 2021)
Health is the primary concern of senior citizens because they might experience many changes and uncertainties that might affect their lives. Further, ageing people tend to forget things, including taking medicine. Failing to follow medication instruction may lead to serious side effects and can worsen their health. The advancement of technologies, especially in mobile applications, could assist senior citizens in managing their health. Therefore, this project proposes a mobile app for senior citizen health monitoring, developed to provide a health monitoring facility for senior citizens by exploiting advanced information and communication technologies. It aims to provide healthcare support for senior citizens to have greater control over monitoring their health. This application assists them daily in their life, such as organizing their medication and taking medicine on schedule with the correct doses. Other than that, the information about their health condition such as allergies, medicine intake, and doctor's information can be accessed quickly from their mobile device in case of emergency. This project was developed using the agile methodology.